2011
DOI: 10.1016/j.cell.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Clan Genomics and the Complex Architecture of Human Disease

Abstract: Human diseases are caused by alleles that encompass the full range of variant types, from single-nucleotide changes to copy-number variants, and these variations span a broad frequency spectrum, from the very rare to the common. The picture emerging from analysis of whole-genome sequences, the 1000 Genomes Project pilot studies, and targeted genomic sequencing derived from very large sample sizes reveals an abundance of rare and private variants. One implication of this realization is that recent mutation may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
310
2
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(328 citation statements)
references
References 116 publications
14
310
2
2
Order By: Relevance
“…However, most of the associated SNPs explain a modest proportion of heritability for most common diseases, 2 and they do not provide variants directly applicable for diagnosis, prevention and treatment. 3 With the advent of whole-genome sequencing, there is now the possibility to evaluate the role of genetic variants that were too rare to be picked up by GWAS. 4 Because rare and potentially deleterious variants arose more recently than common variants, they were not yet eliminated by selection and they might provide most of the medically actionable alleles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the associated SNPs explain a modest proportion of heritability for most common diseases, 2 and they do not provide variants directly applicable for diagnosis, prevention and treatment. 3 With the advent of whole-genome sequencing, there is now the possibility to evaluate the role of genetic variants that were too rare to be picked up by GWAS. 4 Because rare and potentially deleterious variants arose more recently than common variants, they were not yet eliminated by selection and they might provide most of the medically actionable alleles.…”
Section: Introductionmentioning
confidence: 99%
“…4 Because rare and potentially deleterious variants arose more recently than common variants, they were not yet eliminated by selection and they might provide most of the medically actionable alleles. 3,5 These alleles, because of their recent origin, tend to cluster within a lineage and therefore, many disease-related traits have been found in population isolates. 6 Likewise, non-isolated populations displaying fine-scale genetic structure, within a short geographical distance, may be appropriate for gene mapping because they likely present high frequency of rare alleles.…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have speculated that the dramatic increase in the number of new alleles caused by population expansion has altered the genetic architecture of disease and the explanation for missing heritability (42)(43)(44). Specifically, it has been suggested that expansion may have dramatically increased (i) the total frequency of genetic disease by raising mutational load; (ii) the relative importance of new alleles in disease risk; or (iii) the role of rare variants in disease risk.…”
Section: Impact Of Population Expansion On the Genetic Architecture Ofmentioning
confidence: 99%
“…It is likely that genome-wide association studies focusing on common variants and segregation of marker genotypes in populations do not apply when rare variants and de novo gene mutations contribute in a substantial way to a (disease) trait not under selection pressure? 10 The data emerging from genome-wide association studies, including array comparative genomic hybridization and exome sequencing, suggest that both rare variants and new mutations contribute significantly to medically actionable problems. These observations, embedded in the concept of "clan genomics, "…”
Section: Genetics In Medicine | Volume 15 | Number 3 | March 2013mentioning
confidence: 99%
“…10 There is a need to consider a new genetic arithmetic. Even though there is a lack of statistical significance for association (P = 0.26), Moles et al 7 have convinced us of the causality of this duplication CNV.…”
Section: Genetics In Medicine | Volume 15 | Number 3 | March 2013mentioning
confidence: 99%